2018
DOI: 10.1007/s10877-017-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accuracy of noninvasive hemoglobin monitoring for preoperative evaluation between adult and pediatric patients: a retrospective study

Abstract: We measured noninvasive hemoglobin (SpHb) levels during the pre-anesthesia visit in patients planning elective surgery. Differences between SpHb and laboratory-measured hemoglobin (Hb) were compared between adult and pediatric patients. In the pre-anesthesia visiting office, we routinely monitor noninvasive Hb levels with oxygen saturation and heart rate using Masimo Radical-7® Pulse CO-Oximetry (Masimo Corp., Irvine, CA, USA). We attached the R1 20 (body weight, 10-50 kg) or R1 25 (body weight > 30 kg) probe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In acute hemorrhagic patients, SpHb showed significantly lower readings than the laboratory measurement to assess Hb concentration [ 19 , 20 ]. Park YH et al reported that the bias between SpHb and laboratory measured Hb increased with poor peripheral perfusion [ 21 , 22 ]. These results suggest that the limited application of SpHb in critically ill patients may be mainly due to the susceptibility of peripheral spectroscopy signal to impaired tissue perfusion, hypotension, hypothermia, and infusion of vasopressor [ 1 , 5 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In acute hemorrhagic patients, SpHb showed significantly lower readings than the laboratory measurement to assess Hb concentration [ 19 , 20 ]. Park YH et al reported that the bias between SpHb and laboratory measured Hb increased with poor peripheral perfusion [ 21 , 22 ]. These results suggest that the limited application of SpHb in critically ill patients may be mainly due to the susceptibility of peripheral spectroscopy signal to impaired tissue perfusion, hypotension, hypothermia, and infusion of vasopressor [ 1 , 5 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In acute hemorrhagic patients, SpHb showed signi cantly lower readings than the laboratory measurement to assess Hb concentration [19,20]. Park YH et al reported that the bias between SpHb and laboratory measured Hb increased with poor peripheral perfusion [21,22]. These results suggest that the limited application of SpHb in critically ill patients may be mainly due to the susceptibility of peripheral spectroscopy signal to impaired tissue perfusion, hypotension, hypothermia, and infusion of vasopressor [1,5,23].…”
Section: Discussionmentioning
confidence: 99%
“…I think it is time for a revolution in ordering BTs before surgery. The anesthesiologists have noninvasive hemoglobin monitoring [10], along with arterial blood gas, blood sugar, electrolyte assessment, coagulation studies like rotational thromboelastometry (ROTEM), and many other laboratory tests available in seconds in both cardiac and non-cardiac operating rooms(OR). There are new monitoring devices, safer drugs, more available therapeutic options in the OR, expansion of anesthesiologists knowledge in every fields, sophisticated anesthetic drug delivery systems(inhalational and intravenous), and in a word a safer condition for anesthesia management even in currently more difficult cases.…”
Section: Introductionmentioning
confidence: 99%